Analysis of the treatment and prognosis of 266 cases of extranodal natural killer/T-cell lymphoma, nasal type in a single medical center - Yang, Lei; Wei, Liqiang; Li, Xin; Cong, Jia; Ye, Jin; Yao, Na; Yang, Jing; Wang, Liang; Wang, Jingwen (Frontiers in Oncology, 2024)
Objective To assess the impact of different treatment strategies and risk factors on the prognosis of patients with extranodal NK/T-cell lymphoma, nasal type (ENKTL) in a single medical center. Methods and analysis The clinical features of 266 patients with ENKTL were retrospectively analyzed, among whom those in stages I and II received sandwich therapy, while those in stages III and IV underwent chemotherapy plus autologous hematopoietic stem cell transplantation. The Kaplan–Meier curves, univariate and multivariate Cox regression analyses were employed for survival and prognosis analysis. Statistical significance was set at P<0.05. Results Following treatment, the post-intervention outcomes demonstrated a complete remission (CR) rate of 71.05% and a partial remission (PR) rate of 3.76%. The 5-year progression-free survival (PFS) and overall survival (OS) rates were 70.4% and 70.9%, respectively. In addition, the PFS for patients in stage I/II was 79.8%, with an OS of 81.1%, whereas for those in stage III/IV, the PFS was 41.7% and the OS was 40.9%. Notably, the achievement of CR immediately after treatment was an independent prognostic factor (P<0.001). Patients in stage I/II depicted a favorable 5-year OS rate, while those in stage III/IV manifested a less favorable prognosis. Conclusion Stages of the disease and whether CR was achieved following treatment are important factors determining the survival and prognosis of patients with ENKTL. Further researches focusing on disease onset and mechanisms of drug resistance will contribute to better management of ENKTL.